Pengembangan Media Pembelajaran Tabung Pintar Kreatif untuk Meningkatkan Keterampilan Bercerita di TK Aisyiyah VI Kecamatan Baturetno - Tantik, Dewi; Widayati, Mukti; Nurnaningsih, Nurnaningsih (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2025)
This development research aims to describe and describe the development, feasibility, practicality and effectiveness of creative smart tube learning activity media to improve storytelling skills in kindergarten. This development research uses qualitative methods with R&D techniques which refer to the research and development design in Borg and Gall in aten stage research development process. In this development research, the researcher only took seven stages including advantages and problems, combining data, creating media, validating media, improving media, testing media, and revising media. Data collection techniques use observation, question and answer, documentation and bibliography techniques. The results of the accumulated data were then validated using development validation techniques which included the assessment stage of the feasibility results of creative smart tube media carried out by material experts and media experts. The data analysis technique uses qualitative data analysis. From the results of the data description and assessment of the results of development research, a summary conclusion can be drawn, namely: (1) validation of the achievement of the appropriateness of the props by media experts shows a value of 4.35 with an achievement percentage of 87.05% (very feasible), (2) validation of the practicality of the media obtained from group and field trials, (3) validation of media effectiveness obtained from product trials, (4) development of creative smart tube learning media realized in the form of digital learning media, web-based creative smart educational games in the form of numbers, letters and words